VoIP University Solution: VoIP UEMA Project - Oliveira, Carlos Henrique Rodrigues de; Fonseca, Luís Carlos Costa; Torres, Caio de Castro; Pereira, Daniel Gusmão; Ripardo, Luiz Ricardo Souza; Moraes, Magno Castro; Costa, Ana Paula Ferreira; Lima Jr., Luiz Carlos Chaves; Cunha, Aurelianny Almeida da (Anais Estendidos do Simpósio Brasileiro de Redes de Computadores e Sistemas Distribuídos (SBRC), 2024)
VoIP University is a solution to enable the development of communication projects based on IP protocol. This paper presents a low-cost deployment called VoIP UEMA, the first project of VoIP University solution. The technical feasibility of deploying this project was checked in a proof of concept. The concept was proven showing it is possible to create user extensions with information such as name, ID, job role, course, center, and campus get information of all registered users in the academic and administration system server and make voice and video calls through applications for Windows, Android, and iOS. VoIP UEMA project innovates because there is no similar solution in the literature to quadruple play communication that allows integration with any corporate system database to create and manage the user extension list. The low-cost aspect was justified by a financial analysis showing the annual phone bill expense dropped, representing savings of more than 97%.